(untitled) (International Journal of Veterinary Medicine and Animal Science, 2024)
The survey was conducted before the war (before October 2020) in Tigray Regional State, Ethiopia. Indigenous (102 Begait, 106 Hassan and 181 Arado) goat respondents and sheep respondents (126 Begait, 37 Rutanna and 90 Arado) were randomly involved in the head to head interview. Statistical Package for Social Sciences, index ranking and mathematical formulas were used for data analysis. The objective of this survey was to assess flock dynamics, production challenges and opportunities of indigenous goat and sheep populations. Very limited numbers of goat respondents (17% of Begait, 1% of Hassan and 6% of Arado) and sheep respondents (5% of Begait and 7% of Arado) were female headed households. Goat respondents of about 42% of Begait, 29% of Hassan and 55% of Arado were illiterate whereas 25% of Begait, 43% of Hassan and 26% of Arado goat respondents, and 48% of Begait and 57% of Rutanna sheep respondents attended lower primary school. About half (50%) of the Arado sheep respondents were illiterate. The indigenous goat (Begait, Hassan and Arado) and sheep (Begait, Rutanna and Arado) populations were kept under low input extensive production system. Economic contributions ranking of the respondents indicated that goat, cattle and sheep were ranked first, second and third in goat survey whilst sheep, goats and cattle were ranked first, second and third in sheep survey, respectively. Indigenous goat respondents reported that the first, second, and third ranked income sources of the respondents were crop production, goat production, and cattle production, whereas crop production, sheep production, and goat production were the first, second, and third ranked income sources of the indigenous sheep respondents. The major entry in all the indigenous goat and sheep in 2017 production year was additions of newborns to the flocks. Sale and death were the first and second ranked exits in indigenous goats and sheep. Except Hassan goats (+0.1%), flock dynamics (%) in entries and exits of indigenous goat and sheep flocks were at decreasing rates which greatly damaged the economy of the respondents. Begait flock (-16.5%) and Arado flock (-16.7%) goat populations were highly decreased in 2017 production year compared to indigenous sheep flock populations. Respondents of indigenous goat (92% of Begait, 99% of Hassan and 99% of Arado) and sheep (all respondents-100%) reported production challenges and negatively affected productivity. Respondents of indigenous goat (87% of Begait, 80% of Hassan and 38% of Arado) and sheep (76% of Begait, 100% of Rutanna and 53% of Arado respondents) reported production opportunities which could enhance small ruminant productivity. The first, second and third ranked challenges in the indigenous goat and sheep were rangeland scarcity, diseases and lack of veterinary services, respectively. Rangeland scarcity directly negatively affected annual reproductive rate of the indigenous goat and sheep of the study areas. The first, second and third ranked diseases in both goat and sheep were shipping fever, Coenuruses and Contagious Caprine Pleuropneumonia, respectively. The first and second ranked external parasites in both goat and sheep were ticks and fleas whilst the third ranked external parasites in goats was sore mouth and in sheep was jigger flea infestation. Therefore, the diseases, external parasites and challenges should be taken in to account in the designing of genetic improvement of the indigenous goat and sheep of the study areas. Veterinary service centers should also be accessible to all indigenous goat and sheep producers in the study areas.